Strategi, Kerentanan, dan Resiliensi Nafkah Rumahtangga Petani di Daerah Rawan Bencana Banjir - Brigita, Stevani; Sihaloho, Martua (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
Flooding is a natural disaster that provides various impacts on life, especially for the survival of farm households. Farmers in doing the farming certainly depends on the nature and weather. Floods certainly have an impact because it can make the crops decline even to the occurrence of crop failure. Facing such circumstances requires farmers' households to determine the livelihood structures undertaken and demand that farm households determine how to conduct livelihood strategies in order to maintain and improve existing livelihoods. A livelihood strategy is a person's or a group's way of meeting their needs or achieving an improvement in life. The livelihood strategies undertaken will affect the vulnerability of a household and have a relationship with the resilience of the farm household in the event of a flood disaster. Livelihood structures and livelihood strategies of farm households living in flooded areas may be different from those in other areas not experiencing crisis or flood disaster. The purpose of this research is to analyze the strategy, vulnerability and resilience of household livelihoods of farmers in flood-prone areas.Keywords : farm household, livelihood strategy, resilience, vulnerability———————-Â ABSTRAK Banjir merupakan suatu bencana alam yang memberikan berbagai dampak terhadap kehidupan, khususnya bagi keberlangsungan hidup rumahtangga petani. Petani dalam melakukan usahataninya tentunya sangat bergantung dengan keadaan alam dan cuaca sekitar. Bencana banjir tentunya memberi dampak karena dapat membuat hasil panen menurun bahkan sampai terjadinya gagal panen. Menghadapi keadaan tersebut menuntut rumahtangga petani untuk menentukan struktur nafkah yang dilakukan dan menuntut rumahtangga petani menentukan bagaimana melakukan strategi nafkah dalam upaya mempertahankan dan meningkatkan sumber nafkah yang ada. Strategi nafkah adalah cara seseorang atau kelompok untuk memenuhi kebutuhan mereka atau mencapai peningkatan hidup. Strategi nafkah yang dilakukan akan berpengaruh terhadap kerentanan suatu rumahtangga dan memiliki hubungan dengan ketahanan (resiliensi) rumahtangga petani dalam menghadapi situasi bencana banjir. Struktur nafkah dan strategi nafkah rumahtangga petani yang tinggal di kawasan terpapar banjir dapat saja berbeda dengan wilayah lain yang tidak mengalami situasi krisis atau bencana banjir. Tujuan dari penelitian ini adalah untuk menganalisis strategi, kerentanan dan resiliensi nafkah rumahtangga petani di wilayah rawan bencana banjir.Kata Kunci : kerentanan, resiliensi, rumahtangga petani, strategi nafkah